2018
DOI: 10.1126/scitranslmed.aat1662
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnia increases airway smooth muscle contractility via caspase-7–mediated miR-133a–RhoA signaling

Abstract: The elevation of carbon dioxide (CO) in tissues and the bloodstream (hypercapnia) occurs in patients with severe lung diseases, including chronic obstructive pulmonary disease (COPD). Whereas hypercapnia has been recognized as a marker of COPD severity, a role for hypercapnia in disease pathogenesis remains unclear. We provide evidence that CO acts as a signaling molecule in mouse and human airway smooth muscle cells. High CO activated calcium-calpain signaling and consequent smooth muscle cell contraction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(88 citation statements)
references
References 43 publications
2
86
0
Order By: Relevance
“…The clinical parameters values of the patients without wearing masks (group A and group B), including ion concentration of serum, vital signs, in ammation markers and artery blood gas, were showed in Table 2.There were no signi cantly changes inPaCO 2, HCO 3 − act, BE and other parameters between these two hospitalizations. [16]. Hypercapnia could change autonomic nerve function which increase heart rate and blood pressure, especially at higher workloads [17,18].…”
Section: Data Collectingmentioning
confidence: 99%
“…The clinical parameters values of the patients without wearing masks (group A and group B), including ion concentration of serum, vital signs, in ammation markers and artery blood gas, were showed in Table 2.There were no signi cantly changes inPaCO 2, HCO 3 − act, BE and other parameters between these two hospitalizations. [16]. Hypercapnia could change autonomic nerve function which increase heart rate and blood pressure, especially at higher workloads [17,18].…”
Section: Data Collectingmentioning
confidence: 99%
“…The effects of hypercapnia on the airways and airway smooth muscle is complicated. There are reports attesting to it causing increased airway contractility [ 26 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ] or airway relaxation [ 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. We review recent advances in our understanding of how elevated CO 2 conditions modulate the airway tone, focusing on the effects of hypercapnia and respiratory acidosis.…”
Section: Detrimental Effects Of Hypercapnia In Asthmamentioning
confidence: 99%
“…Furthermore, several reports of bronchoconstriction in the hypercapnia-exposed animal models [ 78 , 80 , 82 ] revealed that the blockage of the vagus nerve did not entirely abolish the bronchoconstrictor response to the high CO 2 exposure, suggesting that other mechanisms contribute to the hypercapnia-mediated airway constriction. More recently, we have reported that high CO 2 acts as a signaling molecule to increase smooth muscle contraction in mouse and human airway smooth muscle cells [ 26 ]. We found that high concentrations of CO 2 , independently of hypoxia and extracellular pH, increased acetylcholine-induced cell contraction dependent on CO 2 dose and exposure time in cell culture systems.…”
Section: Detrimental Effects Of Hypercapnia In Asthmamentioning
confidence: 99%
See 2 more Smart Citations